Changes in the bacterial communities of Harmonia axyridis (Coleoptera: Coccinellidae) in response to long-term cold storage and progressive loss of egg viability in cold-stored beetles - Sun, Yuanxing; Hao, Yanan; Wang, Senshan; Chen, Xinling (Frontiers in Microbiology, 2024)
Bacteria have a profound influence on life history and reproduction of numerous insects, while the associations between hosts and bacteria are substantially influenced by environmental pressures. Cold storage is crucial for extending the shelf life of of insects used as tools for biological control, but mostly causes detrimental effects. In this study, we observed a great decrease in egg hatch rate of cold-stored Harmonia axyridis during the later oviposition periods. Furthermore, most eggs produced by their F1 offspring exhibited complete loss of hatchability. We hypothesized that long-term exposure to cold may greatly alter the bacterial community within the reproductive tracts of H. axyridis, which may be an important factor contributing to the loss of egg viability. Through sequencing of the 16S rRNA gene, we discovered considerable changes in the bacterial structure within the reproductive tracts of female cold-stored beetles (LCS_F) compared to non-stored beetles (Control_F), with a notable increase in unclassified_f_Enterobacteriaceae in LCS_F. Furthermore, in accordance with the change of egg hatchability, we observed a slight variation in the microbial community of eggs produced by cold-stored beetles in early (Egg_E) and later (Egg_L) oviposition periods as well as in eggs produced by their F1 offspring (Egg_F1). Functional predictions of the microbial communities revealed a significant decrease in the relative abundance of substance dependence pathway in LCS_F. Moreover, this pathway exhibited relatively lower abundance levels in both Egg_L and Egg_F1 compared to Egg_E. These findings validate that long-term cold storage can greatly modify the bacterial composition within H. axyridis, thereby expanding our understanding of the intricate bacteria-insect host interactions.